Storage system of power grid enterprise based on PBFT blockchain technology - Chunyan YANG; Dongmei BIN; Xin LI (Dianxin kexue)
A blockchain technology based on practical Byzantine fault tolerance (PBFT)algorithm was proposed.First of all, the traditional practical Byzantine fault tolerant algorithm was explained.The traditional algorithm included six phases: pre-stage, demand, pre-preparation, preparation, confirmation, and response.However, traditional algorithms had the disadvantages of poor real-time performance, lack of penalty mechanisms, and high bandwidth.In response to these problems, the traditional algorithm was improved, which specifically involved the accounting node, the consensus process, and the view switching process.The feasibility of the improved algorithm was further proved by testing.Applying this algorithm to power grid enterprises, the federal reserve system was implemented by the constructedvirtual warehouse, which also reduced the consumption of inventory funds.And the efficiency of inventory management in power grid enterprises was improved.